Does Religiosity Influence the Relationship Between Sharia Governance and Member Loyalty in Islamic Cooperatives? - Umuri, Khairil; Halim, Hendra; Farma, Junia; Indah, Cahyani Rahmitha (Tasharruf: Journal Economics and Business of Islam, 2025)
Sharia cooperatives play a pivotal role in advancing Islamic economic development by offering financial services aligned with Islamic principles. Nonetheless, sustaining member loyalty remains a significant challenge. This study investigates the impact of Sharia governance on member loyalty within Sharia cooperatives in Banda Aceh City and examines the moderating role of religiosity in this relationship. Employing an explanatory research design, primary data were collected through questionnaires distributed to 200 purposively selected respondents. The data were analyzed using moderated regression analysis to test the proposed hypotheses. The findings reveal that Sharia governance exerts a positive and significant influence on member loyalty. However, religiosity was found to weaken this relationship, indicating that members with higher levels of religiosity tend to rely more on personal beliefs than institutional governance when forming loyalty. These results suggest that member engagement strategies should not only focus on structural and governance compliance but also incorporate the diverse religious values held by cooperative members. The study offers practical implications for enhancing loyalty in faith-based financial institutions. Limitations include the cross-sectional nature of the data and its geographic restriction to a single region, which may affect the generalizability of the results. Future research is encouraged to include broader contexts and longitudinal data.